al-Istisnāʾ dalam Al-Qur'an Juz 22 (Studi Analisis Sintaksis dan Metode Pembelajarannya) - Chilma Asma Munaya; Yusron Hidayat (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This qualitative library research investigates the forms and variations of al-Istisnāʾ (exception structures) in Juz 22 of the Qur'an through a syntactic and semantic analysis grounded in Arabic grammar (nahwu). The primary data comprise verses from Juz 22, while secondary sources include classical grammar texts, relevant tafsīr literature, and scholarly journals. Data were collected using documentation techniques and analyzed with content analysis methods, employing categorization tools to identify exception elements, particles (adawāt al-istisnāʾ), and exception types. The study identified 38 occurrences of al-Istisnāʾ across four surahs—Al-Aḥzāb, Saba’, Fāṭir, and Yā Sīn—with the particle illā (إِلَّا) being the most frequent (32 instances), followed by ghayr (غَيْر) and the verb lā yakūn (لا يكون). Each instance was examined for structural completeness (involving al-mustasnā minhu, al-adāt, and al-mustasnā) and contextual meaning. The findings reveal both explicit and implicit exception structures, underscoring the Qur’an’s syntactic richness and semantic nuance. Five types of al-Istisnāʾ were identified, with al-mufarraġ being the most prevalent, particularly in emphatic and negating contexts. These variations reflect the Qur’an’s linguistic depth and the critical role of grammatical accuracy in interpretation. The study offers pedagogical insights by recommending inductive and deductive methods in nahwu instruction and advocates the integration of Qur’anic content into grammar teaching. It also proposes the development of thematic learning modules based on Juz 22 to enhance learners’ linguistic proficiency and spiritual engagement.